Retrospective study of onychomycosis patients treated with ciclopirox 8% HPCH and oral antifungals applying artificial intelligence to electronic health records - Gastón Roustan; José Luis López Estébaranz; Pablo De La Cueva; Savana Research Group; Francesca Pajuelo; María Luisa Tamarit; Aida Valmaseda; Jordi Galván (Scientific Reports)
Abstract We conducted a multicenter retrospective analysis of 408 patients diagnosed with onychomycosis who attended three tertiary care Spanish hospitals. The study was conducted to assess the clinical characteristics and outcomes of onychomycosis patients undertaken combined treatment with ciclopirox 8% hydroxypropyl chitosan (CPX 8% HPCH) nail lacquer and oral antifungal agents (terbinafine, itraconazole, and fluconazole). Data were extracted and analyzed using the EHRead® technology based on natural language processing and machine learning and using SNOMED CT terminology. The mean age was 51.1 years, with 54.4% females. Repeated nail trauma was the most common risk factor (7.1%). More than half of the patients (56.6%) underwent fungal culture. Terbinafine, itraconazole, and fluconazole were used in 67.7%, 20.8%, and 11.5% of patients, respectively. Treatment synchronicity distribution revealed that 59.1% of patients started concomitant treatment with CPX 8% HPCH and oral antifungals, 27.9% had initial oral antifungals, and 13% had initial nail lacquer. The response to treatment (positive response 15.7%, presumed positive 59.8%) was unrelated to treatment synchronicity or type of antifungal agent. Erythema (5.6%), diarrhea (4.9%), and fever (4.2%) were the most frequently registered potential adverse events. These findings provide valuable insights for physicians regarding the management of patients with onychomycosis in daily practice.